2005
DOI: 10.1038/433121a
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural ecology: Tool manufacture by naive juvenile crows

Abstract: New Caledonian crows (Corvus moneduloides) are the most prolific avian tool-users. Regional variation in the shape of their tools may be the result of cumulative cultural evolution--a phenomenon considered to be a hallmark of human culture. Here we show that hand-raised juvenile New Caledonian crows spontaneously manufacture and use tools, without any contact with adults of their species or any prior demonstration by humans. Our finding is a crucial step towards producing informed models of cultural transmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(159 citation statements)
references
References 10 publications
7
147
2
3
Order By: Relevance
“…In contrast with the results of Kenward et al (2005) and Kenward et al (2006), we found that the development of proficient Pandanus tool manufacture and use in the wild is a very extended process that is comparable to the ontogeny of tool skills in both human and nonhuman primates. Our findings also suggest that social learning plays an important role in that development.…”
Section: Tool Manufacturecontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast with the results of Kenward et al (2005) and Kenward et al (2006), we found that the development of proficient Pandanus tool manufacture and use in the wild is a very extended process that is comparable to the ontogeny of tool skills in both human and nonhuman primates. Our findings also suggest that social learning plays an important role in that development.…”
Section: Tool Manufacturecontrasting
confidence: 99%
“…One 3-month-old crow manufactured a leaf strip and used it as a probe on its first day of exposure to the leaf (Kenward, Weir, Rutz, & Kacelnik, 2005). Kenward et al (2005) and Kenward et al (2006) therefore concluded that basic tool use and basic Pandanus tool manufacture can develop from a disposition to manipulate tool-like material to try and obtain out-ofreach food, without social input. They cautioned, however, that social learning might play a role in the acquisition of "specific techniques and tool shapes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our preliminary observations have confirmed that ‘Alalā are capable of modifying and manufacturing tools in a variety of ways, paving the way for dedicated experiments that systematically chart the species’ natural tool-making repertoire, as well as its ontogenetic development [4,2224]. Importantly, subjects need to be tested under conditions where they have access to a wide variety of naturalistic foraging tasks (including those routinely encountered by wild New Caledonian crows [2,3,11,12,16]), and different plant materials for tool manufacture, but not to sticks or other objects that could be used as tools without further processing (as was the case in our first study [4]).…”
mentioning
confidence: 68%